Character traits and involvement in immoral acts among adult Malay prisoners in Kajang Prison, Malaysia - Laidin, Jamaliah (2010)
A quantitative study on Malay adult prisoners’ involvement in immoral acts from internal factors such as Islamic character traits perspective whether related or contributory to the involvement in immoral acts has never been explored. Al Ghazali’s ethical theory is used as basis for this study. The objective of the study is to identify the mahmudah and mazmumah character traits among Malay adult prisoners and to describe their relationship with immoral acts involvement. The study involves a total of 801 respondents through random sampling are chosen from the Kajang Prison inmates in the Klang Valley. The study adopts a correlational research design. The Inventori Tret Watak or the Character Traits Inventory, a self-administered questionnaire developed by the researcher, is used. It consists of 108 items with seven constructs. Six constructs represent Islamic character traits under the respective faculties of:ghadab mahmudah (M), ghadab mazmumah (E-D); syahwat mahmudah (M),syahwat mazmumah (E-D); and ‘ilm/’aql mahmudah (M), ‘ilm/’aql mazmumah ghadab mahmudah (M), ghadab mazmumah (E-D); syahwat mahmudah (M),syahwat mazmumah (E-D); and ‘ilm/’aql mahmudah (M), ‘ilm/’aql mazmumah (E-D); while one construct of ghadab-syahwat-syaitaniyyah (D-E-S) represents immoral acts involvement. They are developed with the use of factor analysis. Pearson Product Moment Correlation Coefficient shows a significant positive relationship between immoral acts involvement and total mazmumah ghadab (E-D) character traits (r =.47; p<.01). It also shows a significant positive relationship between immoral acts involvement and total mazmumah syahwat (E-D) character traits (r =.39; p<.01). The strength of the correlation of both the total mazmumah character traits of ghadab and syahwat are of medium strength. There is also a significant positive relationship between immoral acts involvement and total mazmumah ‘ilm/’aql (E--D) character traits (r=.10; p<.01). The strength of the correlation is of small strength. Pearson Product Moment Correlation Coefficient also shows a significant negative relationship between immoral acts involvement and total mahmudah ghadab (M) character traits (r = -.11; p<.01) and a significant negative relationship between immoral acts involvement and total mahmudah syahwat (M) character traits (r = -.12; p<.01). It also found that there is a significant negative relationship between immoral acts involvement and total mahmudah ‘ilm/’aql (M) character traits (r= -.09; p<.05). The strength of the correlation of all the three total mahmudah character traits is of small strength.(E-D); while one construct of ghadab-syahwat-syaitaniyyah (D-E-S) represents immoral acts involvement. They are developed with the use of factor analysis. Pearson Product Moment Correlation Coefficient shows a significant positive relationship between immoral acts involvement and total mazmumah ghadab (E-D) character traits (r =.47; p<.01). It also shows a significant positive relationship between immoral acts involvement and total mazmumah syahwat (E-D) character traits (r =.39; p<.01). The strength of the correlation of both the total mazmumah character traits of ghadab and syahwat are of medium strength. There is also a significant positive relationship between immoral acts involvement and total mazmumah ‘ilm/’aql (E--D) character traits (r=.10; p<.01). The strength of the correlation is of small strength. Pearson Product Moment Correlation Coefficient also shows a significant negative relationship between immoral acts involvement and total mahmudah ghadab (M) character traits (r = -.11; p<.01) and a significant negative relationship between immoral acts involvement and total mahmudah syahwat (M) character traits (r = -.12; p<.01). It also found that there is a significant negative relationship between immoral acts involvement and total mahmudah ‘ilm/’aql (M) character traits (r= -.09; p<.05). The strength of the correlation of all the three total mahmudah character traits is of small strength. Multiple linear regression analysis shows that seven predictors of the Islamic character traits contribute significantly towards immoral acts involvement among Malay adult prisoner respondents. The seven predictors are the mazmumah ghadab (E), mazmumah syahwat (E), mahmudah ghadab (M),mahmudah syahwat (M), mazmumah ghadab (D), mazmumah syahwat (D) and mazmumah ‘ilm/’aql (D). They are ignificant predictors of immoral acts involvement [R2 = .73, F (9, 583) = 171.464; p< .05]. The study focuses on an overall relationship between the Malay adult prisoner respondents’ character traits and crimes committed without linking the character traits to specific crimes. Based on the findings of the study the researcher suggests that the teaching of akhlak in Islamic studies for the Malay adult prisoner respondents in Kajang Prison should be focused on the development of Islamic moral character traits and character.